Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1997)
Table of Content : Trickster Eva Hesse by Ursula Panhans-Bühler ; Clockwork (Jon Kessler) by Douglas Blau ; Stephan Balkenhol : Stephan Balkenhol, The Figure as Witness by Neal Benezera As Time goes by by Vik Muniz Autonomous ; People by Max Katz 57 Penguins by Jean-Christophe Ammann ; Sophie Calle : Sophie Calle’s Uncertainty Principle by Luc Sante ; Postcards to Sophie Calle by Joseph Grigely ; The Hpyerfiction of Life and Death by Patrick Frey ; Sophie Calle’s and Gregory Shepard’s Double Blind by Robert Beck ; Richmond Burton, Insert Dimensions Variable: Liz Larner by Robert Beck ; Rudolf Schwarzkogler by László Földényi Berlin – Fast Forward, Cumulus from Europe by Christoph Tannert ; Nobody Wants to See a Movie with Madonna in It, Cumulus from America by David Rimanelli ; The Applied Art of Animal Breeding by Alexander Popper
Selected Realities. In a recent photograph, Douglas Gordon appears wearing a poorly fitting blonde woman’s wig. This set piece allows him to try on several identities in the imaginary mirror of popular culture: The title, SELF-PORTRAIT AS KURT COBAIN, AS ANDY WARHOL, AS MIRA HINDLEY, AS MARILYN MONROE, transports the picture into the region of psycho-symmetries. Mirrored and mirroring: The cover of Parkett also appears in the guise of an idea suggested by Douglas Gordon. The simple device preempts Parkett’s customary appearance as a reminder that alienation is reflection’s constant companion. The Parkett logo—for those who always wanted to know: it is embroidered—and the other lettering on the cover are “out of sync” as well. Contrary to custom, the collaboration artists are not presented in alphabetical order. The placement of Jeff Wall in the middle and Laurie Anderson at the end of the volume is motivated not by the idea of inversion but quite simply by the fact that their pictorial realities lend themselves to reproduction in such different ways. All three artists make use of optical equipment but only in Jeff Wall’s work is the final product a static image, while Laurie Anderson and Douglas Gordon often rely on clearly defined temporal continuums. Since the reproduction of their art in the pages of a magazine is as difficult as it is misleading, we have decided to present Jeff Wall’s compelling tableaux as a visually distinctive center. All three artists engage reality with an intensity that exposes its inherent plurality. In Jeff Wall’s meticulously constructed slices of life, everyday life rubs against art and art history. A SUDDEN GUST OF WIND, in which the elements wreak havoc with a business man’s papers, reflects the motif of a famous woodcut by the Japanese artist Hokusai (1760-1849). A painterly canon of contemporary connotations emerges (editorial by publisher)
boek
Keywords: Anderson, Laurie; Wall, Jeff; Gordon, Douglas